Captive audience the telecom industry and monopoly power in the new gilded age - Crawford, Susan P. (Yale University Press, 2013)
Ten years ago, the United States stood at the forefront of the Internet revolution. With some of the fastest speeds and lowest prices in the world for high-speed Internet access, the nation was poised to be the global leader in the new knowledge-based economy. This important book by leading telecommunications policy expert Susan Crawford explores why Americans are now paying much more but getting much less.